The Effect of H₂SO₄ Catalyst and Electric Voltage on Hydrogen Gas Production via the Electrolysis of Distilled Water - Siti Kotijah; Difa Adanisa; Sri Redjeki (Universitas Islam Raden Rahmat, Malang, 2025)
Hydrogen is an environmentally friendly alternative energy source with great potential in the renewable energy sector. One efficient method for hydrogen production is water electrolysis, which can be influenced by catalyst concentration and applied electric voltage. This study aims to analyze the effect of varying H₂SO₄ concentrations and electric voltage on hydrogen production via water electrolysis. The concentrations used were 0.05 M, 0.075 M, 0.1 M, 0.25 M, and 0.5 M, while the applied voltages were 16 V, 18 V, 20 V, 22 V, and 24 V. Constant parameters included 500 mL of distilled water and a 2-minute hydrogen collection time. Gas analysis using Gas Chromatography-Thermal Conductivity Detector (GC-TCD) showed hydrogen detection at a retention time of 2.88 minutes. The highest hydrogen content, 11.143% mol, was achieved at 0.075 M H₂SO₄ and 24 V, with a maximum gas volume of 0.000659 m³. Based on RSNI ISO 14687:2019, the minimum fuel-grade hydrogen requirement is 50% mol. Therefore, further optimization is necessary to improve efficiency. Future studies are recommended to explore alternative catalysts, extend electrolysis time, or modify electrodes, as well as include tests without catalysts to evaluate reaction sustainability and compare hydrogen yields with and without catalytic influence.